Ras is required for a limited number of cell fates and not for general proliferation in Caenorhabditis elegans. - Yochem, J (1997)
Experiments with mammalian tissue culture cells have implicated the small GTPase Ras in the control of cellular proliferation. Evidence is presented here that this is not the case for a living animal, the nematode Caenorhabditis elegans: proliferation late in embryogenesis and throughout the four larval stages is not noticeably affected in animals lacking Ras in various parts of their cell lineages. Instead, genetic mosaic analysis of the let-60 gene suggests that Ras is required only, at least later in development (a maternal effect cannot be excluded), for establishment of a few temporally and spatially distinct cell fates. Only one of these, the duct cell fate, appears to be essential for viability.